2018
DOI: 10.1016/j.eurpsy.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting suicidal behaviour after first episode of non-affective psychosis: The role of neurocognitive functioning

Abstract: GCF was found to be the most robust predictor of SB along with severe depressive symptomatology. Hence, poorer cognitive performance in FEP appears to emerge as a risk factor for suicidal behaviour from early stages of the illness and a comprehensive neurocognitive assessment may contribute to risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 48 publications
1
43
1
1
Order By: Relevance
“…Suicide attempters may have different neurocognitive characteristics than non-attempters, which suggests that comprehensive neurocognitive assessments are needed to investigate their relationship. 37 Furthermore, the cognitive performance of SCZ patients varies over time. 38 Meanwhile, impairments in the serotonin neurotransmitter system and the hypothalamicpituitary-adrenal axis stress response system significantly affect cognitive performance, 39 which could lead to changes in cognitive function in SCZ patients, regardless of suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide attempters may have different neurocognitive characteristics than non-attempters, which suggests that comprehensive neurocognitive assessments are needed to investigate their relationship. 37 Furthermore, the cognitive performance of SCZ patients varies over time. 38 Meanwhile, impairments in the serotonin neurotransmitter system and the hypothalamicpituitary-adrenal axis stress response system significantly affect cognitive performance, 39 which could lead to changes in cognitive function in SCZ patients, regardless of suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the severity of depressive symptoms was the most robust risk factor of suicidal behaviors in psychiatric disease 46,47 . Accordingly, a study of long-term hospitalized SCZ patients in China found that 72% of suicidal attempts were accompanied by depressive symptoms 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that the severity of negative symptoms was lower in schizophrenia patients who attempted suicide (37). With respect to cognitive performance, decreased global cognitive functioning and visual memory predicted suicidal behavior in non-affective psychosis (38). In a meta-analysis and meta-regression analysis in over 80,000 patients with schizophrenia, depressive symptoms, the Positive and Negative Symptom Scale (PANSS) general score, and the number of hospitalizations were higher in patients with suicidal ideation (39).…”
Section: Mortality In Schizophreniamentioning
confidence: 99%